P156NLRP3 mediates cardio-protection during ischemia-reperfusion. (15th July 2014) - Sandanger, O; Gao, E; Ranheim, T; Bliksoen, M; Kaasboll, OJ; Alfsnes, K; Lien, E; Aukrust, P; Vinge, LE; Yndestad, A
Abstract: Background: NLRP3 is an innate immune receptor that recognizes tissue damage and initiate inflammatory processes: chiefly, upon activation, NLRP3 forms multiprotein complexes with the adaptor protein ASC and caspase-1, termed inflammasomes, which cleaves pro-IL-1β and mediates release of bioactive IL-1β. Thus, NLRP3 activation may lead to further tissue damage. Hence, we hypothesized that NLRP3 mediates tissue damage during acute myocardial infarction and sought to investigate the mechanisms herein. Methods: The LAD of WT, NLRP3 KO and ASC KO mice of both genders were sham-operated or ligated in vivo for 30 minutes followed by 3 or 24 hours reperfusion. For pre-conditioning studies, the TLR2 agonist Pam3Cys or PBS was injected intraperitoneally 60 minutes prior to LAD ligation. In animals subjected to 24 hours reperfusion, the LAD was re-ligated in vivo and non-ischemic tissue stained by retrograde perfusion of Evans Blue in the aorta. The area at risk was stained after slicing with TTC, revealing the area of non-stained tissue as the infarct size. For further mechanistic investigations, blood plasmas and left ventricle tissues were collected and a hypothesis-driven selection of protein or mRNA targets were investigated with Western blot, ELISA, bioplex or PCR. Results: No difference in the area at risk was observed between any groups. Surprisingly, hearts from NLRP3 -and ASC deficient mice featured larger infarct size than that of WT mice (p=0.0048 and not statistically significant [p=0.0840], respectively). Furthermore, preconditioning with the TLR2 agonist Pam3Cys reduced infarct size in WT but not NLRP3 -or ASC -deficient hearts. There was no difference in plasma troponin I, IL-1β or IL-1α between any groups at 3 or 24 hours. In accordance with this, there were similar corresponding mRNA levels in cardiac tissue. However, there were significantly higher levels of CXCL1 in plasma from NLRP3-deficient mice at 3 hours. Preconditioning with Pam3Cys and MI for 30 min, resulted in increased phosphorylation of the cardioprotective kinase AKT in WT mice. However, this was not observed in NLRP3 -or ASC deficient mice, indicating a role for the NLRP3 inflammasome in cardioprotection. Conclusion: Absence of NLRP3 results in increased myocardial infarct size after in vivo ischemia reperfusion, seemingly due to dysfunction of the cardio-protective p-AKT signalling pathway involved in preconditioning. Furthermore, increased CXCL1 chemokine release may result in more tissue damage due to recruitment of neutrophils. Hence, our data imply that NRLP3 contribute to cardio-protection during ischemia-reperfusion.